Night at the museum. Secret of the tomb [videorecording (DVD)] - Stiller, Ben, 1965-; Williams, Robin, 1951-2014; Wilson, Owen, 1968-
Get ready for the wildest and most adventure-filled night as Larry spans the globe, uniting favorite and new characters while embarking on an epic quest to save the magic before it is gone forever.